ENERGY POLICY TODAY AND TOMORROW— TOWARD SUSTAINABILITY? (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} In 1991, Wendell Berry wrote: “Under the rule of the ‘free market’ ideology, we have gone through two decades of an energy crisis without an effective energy policy. Because of an easy and thoughtless reliance on imported oil, we have no adequate policy for the conservation of gasoline and other petroleum products. We have no adequate policy for the development or use of other, less harmful forms of energy.” Berry’s assertion—that by the early 1990s our nation had become entrenched in what was, effectively, no real cohesive energy policy—rang true then, when the 1973 Arab oil embargo was still relatively recent history and the 1990–91 Gulf War was barely in the rearview mirror. But looking forward rather than back, standing on the edge of this century’s next decade, it reminds me of another refrain from a very different context. Two years after Berry penned his words, a panel of the D.C. Circuit gave the Federal Energy Regulatory Commission (“FERC”) a decided tongue-lashing on a narrow question of administrative law and utility ratemaking that, it seemed, was intended to sting.